THE EFFECT OF PLANT SPACING AND PHOSPHOROUS DOSAGE ON GROWTH AND YIELD OF PEANUT (Arachis hypogea L.) - Ayu Dita Rani; Kharis Triyono; Sumarmi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
This study aims to find out the effect of plant spacing and phosphorous dosage on growth and yield of peanut (Arachishypogea L.). The research was carried out at Bleboh, Jiken, Blora from February 19th to May 26th 2022. Using 2 factorof Randomized Complete Block Design (RCBD) and 3 repetition. Plant spacing (J) as factor 1 consisted of 3 levels, namelyJ1 = plant spacing 40 × 10 cm, J2 = plant spacing 40 × 15 cm, J3 = plant spacing 40 × 25 cm. Phosphorous dosage (D) asfactor 2 consisted 4 levels, namely D0 = (Control), D1 = phosphorous dosage at 75 kg/ha, D2 = phosphorous dosage at 150kg/ha , D3 = phosphorous dosage at 225 kg/ha. The data were analyzed using analysis of variance with a further BNJ testwith a level of = 5%. The result showed plant spacing (J) affected to all parameters except number of empty pods per plant,which plant spacing 40 × 10 cm (J1) had the best result in plant height and pods weight per plot, whereas plant spacing 40 ×25 cm (J3) had the best result in number of pods per plant, number of pithy pods per plant, pods weight per plant, seedsweight per plant and 100 seeds weight. Phosphorous dosage (D) affected to all parameters except plant height, with the bestdose is 150 kg/ha.Keywords: phosphorous dosage, plant spacing, peanut.